Plan de gestión ambiental para los emprendimientos turísticos del humedal la Segua - Ormaza Medina, Jonathan Steven (2019)
The purpose of this research was to develop an environmental management plan for tourism ventures in the Segua wetland. For its effect, 3 phases were structured according to the objectives: the first one corresponded to the diagnosis of the La Segua wetland ventures, which allowed the identification of 21 ventures between restaurants, cafes, kiosks and recreational centers where the low tourist offer is especially reflected of accommodation and problems linked to the lack of organization, control and evaluation, especially in matters of environmental management, characterized as deficient. In the second stage the structure of the plan was determined, for this a review of official documents was carried out to gather information based on indicators, determining a total of 19 environmental sustainability indicators duly assessed by a group of experts. In the third stage the environmental management plan was designed as a final proposal that included the formulation of a general objective and three specific objectives, followed by the plan with a total of 4 programs depending on the water, air, energy and soil resources, subjects to the indicators defined by the experts, directing the actions proposed based on the tourism ventures of the La Segua wetland, determining deadlines and responsible parties in order to commit the main actors and solve the problem.